Activation of Business and Institutionalization of the Red-and-White Village Cooperatives in the Kolono District, South Konawe Regency - Nur, Syamsir; Ernawati; Saranani, Fajar; Barani, Laode Samsul; Anam, Syamsul; Anjasari, Meilan (CV. Literasi Indonesia, 2025)
The Red-and-White Village Cooperatives has strategic potential as a forum for the people's economy that plays a role in improving the welfare of rural communities, creating jobs, expanding economic participation, accelerating the strengthening of MSMEs, and reducing inflation and extreme poverty. However, its establishment and sustainability face a number of challenges, particularly related to business aspects, the quality of management resources, institutional aspects, and partnership networks. This activity aims to improve the business and institutional capacity of its managers so that cooperatives can operate as transparent, accountable, sustainable economic entities based on local potential. The expected benefits include increased understanding and skills in cooperative governance, particularly in business and institutional management, as well as support for local governments in strengthening the role of cooperatives as pillars of family-based and mutual assistance economic empowerment. The results show that Kolono Subdistrict has 21 Red-and-White Village Cooperatives, all of which were established through a new cooperative establishment model in accordance with the Minister of Cooperatives Implementation Guidelines Number 1 of 2025. The existence of these cooperatives is supported by government support, institutional structures, local resource potential, and market opportunities. However, several obstacles remain, such as low management and human resource capacity, limited capital, minimal member participation, and market uncertainty. Business and institutional activation needs to be directed towards strengthening governance, increasing human resource capacity, developing relevant business models, utilizing technology, strengthening capital, multi-stakeholder collaboration, and continuous monitoring and evaluation.